Sistem Pendukung Keputusan Pemilihan Objek Wisata Menggunakan Metode AHP - Anwar, Shobun Kollied; Priyanto, Agus; Ramdani, Cepi (STIKOM Tunas Bangsa Pematangsiantar, 2021)
Purwokerto is an interesting city to visit because it has many tourist attractions that offer natural beauty. Many tourists visiting Purwokerto have difficulty getting information about tourist objects and determining tourist destinations. This is based on the results of a survey of 114 respondents. Based on these problems, we need a system that provides information and provides recommendations regarding tourist destinations. The system is designed by applying the Analytical Hierarchy Process (AHP) algorithmas an algorithm that selects tourist destinations based on the criteria entered by the user. As for the methoddevelopment The software used in this research is a method Waterfall. Which systemhas beenbuilt tested to users using the User Acceptance Test testing method. This is meant to mengmeasure user acceptance. UAT testing conducted on 100 respondents measured 3 aspects, namely, software engineering aspects, functionality aspects, and visual communication aspectsal gives a value of 5,660. The value is converted using the Likert's Summated Rating (LSR) method, giving the conclusion that the system that has been built is accepted by the user.